Using life cycle assessment for estimating environmental impacts and eco-costs from the metal waste in the construction industry. Issue 2 (14th March 2016) - Yahya, Khairulzan; Boussabaine, Halim; Alzaed, Ali Nasser
Abstract : Purpose: – The purpose of this paper is to investigate how to estimate the ecological costs form metal waste based on life cycle assessment (LCA) environmental impacts generated from the management of the construction waste. Design/methodology/approach: – LCA methodology and eco-indicators 95 were used to calculate the impact from metal waste based on three waste management strategies. Findings: – The results of this study establish that the ecological impact from metal waste management is mainly due to the burning of diesel from machinery during the dismantling processes and the use of vehicles for transportation. The results proposed equations and curves for estimating the ecological cost from metal waste based on waste management strategies. Research limitations/implications: – The research could affect members of the engineering and construction industry, since it provides methods for costing the ecological impact from construction waste. The eco-costs will assist in implementing sustainable strategies that help to reduce the amount of waste generated by the construction industry. Originality/value: – This paper presents an exploratory study to conceptualise eco-costing issues in relation to waste from construction activities in the UK construction industry.